2021
DOI: 10.3390/foods11010011
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics Profile, Antioxidant Activity and Flavor Volatiles of Pear Juice: Influence of Lactic Acid Fermentation Using Three Lactobacillus Strains in Monoculture and Binary Mixture

Abstract: The aim of this study was to evaluate the effects of lactic acid fermentation using three Lactobacillus strains (Lactiplantibacillus plantarum 90, Lactobacillus helveticus 76, and Lacticaseibacillus casei 37) in monoculture and binary mixture on phenolics profile, antioxidant activity and flavor volatiles in pear juice. Results showed that the colony counts of binary mixture were higher than monoculture in fermented pear juice. The total content of phenols was increased, while that of flavonoids was decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Laureys & De Vuyst (2016) also stated that aldehydes such as hexanal, furfural and benzaldehyde, which they detected before fermentation, were not found in water kefir after fermentation. Alike our results, Wang, Zhang & Lei (2021) determined that ketones and aldehydes reduced in all fermented pear juices. It can be said that the reduction of aldehydes and ketones results from their degradation or oxidation to alcohols or acids by LAB metabolism ( Xu, Bao, Wu, Lao, Hu & Wu, 2019 ).…”
Section: Resultssupporting
confidence: 85%
“…Laureys & De Vuyst (2016) also stated that aldehydes such as hexanal, furfural and benzaldehyde, which they detected before fermentation, were not found in water kefir after fermentation. Alike our results, Wang, Zhang & Lei (2021) determined that ketones and aldehydes reduced in all fermented pear juices. It can be said that the reduction of aldehydes and ketones results from their degradation or oxidation to alcohols or acids by LAB metabolism ( Xu, Bao, Wu, Lao, Hu & Wu, 2019 ).…”
Section: Resultssupporting
confidence: 85%
“…Thirteen esters were detected in PAJ, and the most dominant of which was 2-methylbutyl acetate, the characteristic substance in fresh apple juice aroma. 2-methylbutyl acetate imparts fruity and sweet aromas to the juice ( 48 ). Other prominent esters in PAJ, such as ethyl butyrate, ethyl 2-methylbutyrate, hexyl acetate, nonyl acetate, and 2-phenylethyl acetate, were almost completely consumed during the fermentation of L. paracasei and L. plantarum .…”
Section: Resultsmentioning
confidence: 99%
“…With the development of the fruit, Arbutin, Catechin, Chlorogenic acid, Epicatechin, Kaempferol hexoside-dideoxyhexoside, Rutin, Kaempferol-3-O-rutino side, Quercitrin, Quercetin rhamnoside, Isorhamnetin-3-O-rutinoside, Kaempferol-3-O-glucoside, Isorhamnetin-3-O-glucoside, Kaempferol-3-acetylglucoside, Isorhamne tin-3-acetylhexoside were detected in the four pear fruit species (Figure 3), the 14 phenolic compounds were highest in the young fruit growing stage (5/25-6/22), among which arbutin and chlorogenic acid were the main components of pear fruit phenolics, and arbutin was the highest, in line with the trend for total phenols and total flavonoids. Wang et al (19) also found the highest levels of arbutin and chlorogenic acid in a study of 10 pear varieties, and Zhang and Liu (27) used Yali as samples and also demonstrated that arbutin and chlorogenic acid are the main phenolic substances in pear fruit. In the young fruit stage, the highest arbutin and chlorogenic acid content was found in the Nanguo pear and the Aksu Juju pear, which were 14104.22 µg/g DW, 22403.53 µg/g DW and 10614.57 µg/g DW, 6761.10 µg/g DW, followed by 8,281.87 µg/g DW and 3,816.91 µg/g DW for the Luntai Juju pear, and the lowest 5,663.91 µg/g DW and 2013.04 µg/g DW for the Hongxiang pear.…”
Section: Composition and Content Of Phenolics In Pear Fruit During Gr...mentioning
confidence: 94%
“…These pear fruits are sweet and juicy, fragrant and refreshing, crispy and less residue, and rich in phenolic substances with strong antioxidant activity, such as chlorogenic acid, rutin, epicatechin, catechin, etc. consumer favorite (19). The antioxidative and anti-melanin deposition effects of fragrant pear provide a good pharmacodynamic basis for the research and development of antioxidative and whitening cosmetic products.…”
Section: Introductionmentioning
confidence: 99%